Fantástico y terror: teoría y práctica de dos categorías ficcionales en el ámbito hispánico - Carrera Garrido, Miguel (Studia Romanica Posnaniensia, 2018)
In the studies of non-mimetic fiction in the Hispanic world, reflections on expressions traditionally considered popular have been consolidating little by little. It is striking that, in this process of academic visibilization, such scarce attention is paid to horror. Often associated with the category of the fantastic, it urges to claim the specificity of this genre as an expression similar to the fantastic; not coincident with it, but, on the contrary, endowed with particular features. The purpose of the article is precisely to illustrate these characteristics. To this end, we resort to sources of various kinds, including those that assume the specific character of horror, and those that study it as part of the fantastic mode. All of them will contribute to the establishment of a solid theoretical basis; once it is fixed, we will proceed to exemplification by means of the analysis of two stories belonging to each of the categories and by the same author: Cádiz-born Félix J. Palma (Sanlúcar de Barrameda, 1968).